John from Cincinnati - Milch, David 1945-; Nunn, Kem (Home Box Office, Inc., 2008)
"In Imperial Beach, California, the dysfunctional Yost family intersects with two new arrivals to the community: a dim-but-wealthy surfing enthusiast and man spurned by the Yosts years ago." [imd.com]
Original: USA 2007-
Keywords: Film